PERFIL ALIMENTAR, AVALIAÇÃO DO FLUXO SALIVAR E XEROSTOMIA EM MULHERES NO CLIMATÉRIO USUÁRIAS E NÃO USUÁRIAS DE TERAPIA DE REPOSIÇÃO HORMONAL - Labidi, Afef Tlili (2012)
INTRODUCTION: In climateric, there are sweeping changes that can be felt also in the oral cavity by hyposalivation or xerostomia, which can be minimized with Hormone Replacement Therapy (HRT). The dietary profile in premenopausal women helps prevent the most prevalent diseases in this age group. Therefore, the analysis of food consumption in premenopausal women helps deepen new approaches to dietary intervention for the prevention and control, enabling them a better quality of life. OBJECTIVES: We aim to investigate the dietary profile and the relationship between low flow rate of saliva and xerostomia in menopausal women users and nonusers of HRT. METHODS: Cross and prospective research by the application of questionnaires and salivary flow analysis in menopausal women who attended the University Hospital of UFMA in 2009 and 2010. They were divided into two groups A and B. Group A was composed of women using HRT and Group B for non-users. RESULTS: Group A had a higher volume of salivary flow compared with Group B (p = 0.021). Xerostomia was found to be a symptom independent of salivary flow rate, and was present mostly in Group B. The highest mean BMI was found in Group B. The consumption of sugars and fats dominated in obese type II, in thin vegetables, of fruits in overweight, and of milk and dairy products in normal weight. CONCLUSIONS: Based on the assessment of dietary consumption, this study showed that menopausal women eat incorrectly in quantitative and qualitative terms, with a trend toward greater consumption of fats. We also conclude that HRT is beneficial regarding symptoms of dry mouth and increase of salivary flow.